Pengelolaan Keuangan Melalui Aplikasi Moni dalam Meningkatkan Kompetensi UMKM pada Era Digital - Tikaromah, Oom; Yahya, Adibah; Yuningsih, Nining; Tsaran, Annisa Putri; Lutfi, Adilista Puspa Aliya; Yuliani, Reva (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2025)
Abstract: Micro, Small and Medium Enterprises (MSMEs) are a vital sector that contributes significantly to the Indonesian economy, but often face internal obstacles, particularly in terms of governance and financial management, which are not yet orderly. Although the population's financial literacy is quite good, practical understanding in the field, especially among MSMEs, is still low, exacerbated by a lack of digital literacy skills to take advantage of the rapid development of financial applications. Therefore, this community service activity aims to improve the competence of MSMEs in business and financial management through the use of digital technology. The methods used include observation and interviews to identify needs, followed by basic financial management training and intensive assistance in using the Moni application. Moni was chosen because it is designed to be intuitive, affordable, and provide real-time financial analysis. The results of the activity show a positive and significant impact on MSME partners, who previously faced problems with manual recording and mixing of finances, but are now gradually adopting digital transaction recording, indicating an increase in awareness and competence in managing business finances using technology.